Tourist Attraction and Tourist Facilities Intentions to Visitor Satisfaction: Case of Sindang Barang Cultural Village - Simanihuruk, Maidar (E-Journal of Tourism, 2019)
The tourist attraction and tourist facilities provided at the Sindang Barang Cultural Village have a positive influence and significantly contributed to visitor satisfaction, which can attract tourists and visitors to come to this place. The research was conducted at the Sindang Barang Cultural Village. The purpose of this study is to determine the impact of tourist attraction and tourist facilities on visitor satisfaction at the Sindang Barang Cultural Village. The Method of research used is quantitative methods in order to obtain more comprehensive, valid, reliable, and objective data. The sample consists of 107 visitors who visited the Sindang Barang Cultural Village. The factor and regression analysis were used for the data analysis. The results of the study showed that tourist attraction significantly contributed to the visitors? satisfaction (t = 10.180 > t table with a significance of 0.000 (? < 0.05). Tourist facilities significantly contributed to visitors? satisfaction (t = 4,082 > t table with a significance of 0.000 (? < 0.05). The tourist attraction and tourist facilities have a significant effect simultaneously on Visitors? satisfaction (F= 149.205 > F table with a significance of 0.000 < 0.05. Tourist attraction at the Sindang Barang Cultural Village has a dominant influence in influencing visitor satisfaction with the uniqueness and characteristics of Sunda Tradition Ritual Tourist Attraction which is the hallmark of the Sindang Barang Cultural Village. The Tourist facilities show that this variable is a variable that affects visitor satisfaction where the facilities available for the information center are still not fully available. The author makes a suggestion, recommend paying more attention and developing facilities that provide complete information about the Sindang Barang Cultural Village. Keywords: Tourist Attraction, Tourist Facilities, Visitor Satisfaction, Cultural Village, Sindang Barang